ANALISIS PENCAHAYAAN ALAMI RUMAH HUNIAN YANG BERADA DI ABIANSEMAL,BALI MENGGUNAKAN DIALUX - Irfan Dwi Cahyono; Sutrisno; Achmad Nur Hasyim; Achmad Zidan Dwi Ismail; Adilla Rava Naura Ayu; Tee Tze Kiong (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the performance of natural lighting in residential houses located in Abiansemal District, Bali, by considering the influence of building orientation, opening configuration, and light distribution within the room. Natural lighting is an important aspect in improving visual comfort as well as energy efficiency in residential buildings. The research method used is a quantitative approach with descriptive techniques through direct measurements using a lux meter at three observation times, namely 08.00, 12.00, and 15.00 WITA. The data obtained were processed by calculating the average illuminance value in each room, then compared with the natural lighting standard based on SNI 6197:2020. The results showed a significant variation in lighting levels between rooms, where the living room and kitchen had an average illuminance value of 168.1 lux and 136.7 lux, respectively, thus meeting the established standards, while the front bedroom and back bedroom showed an average value of 97.2 lux and 50.0 lux, respectively, which were still below the standard. This difference is influenced by the position of the room relative to the natural light source and the type of lighting access, both direct and indirect. These findings confirm that rooms with direct openings to the outside environment have more optimal lighting performance than rooms that rely on internal openings. Therefore, designing effective openings and adjusting building orientation are crucial factors in improving the quality of natural lighting in residential homes.